Novel insights into the evolution and structural characterization of dyskerin using comprehensive bioinformatics analysis - Cerrudo, Carolina Susana (2015)
Dyskerin is a conserved nucleolar protein. Several related genetic diseases are caused by defects in dyskerin. We hypothesized that having a comprehensive bioinformatic analysis of dyskerin will help to develop new drugs for this diseases. We predicted protein domains and compared sequences and structures to detect the universe of dyskerin-like proteins. We identified conserved features of shared domains in the three superkingdoms. We analyzed the phylogenetic diversity, confirming that there is a strong structural conservation. Also, we studied the relationship of dyskerin-like proteins with other proteins through an integrative protein-protein interaction approach. Most of them are conserved among homologous eukaryotic and archaeal proteins. Our results highlighted the preservation of proteins interacting with dyskerin. We identified conserved dyskerin interactor proteins between the different eukaryotes organisms. Furthermore, we studied the existence of dyskerin-like proteins in different species. Also, we compared and analyzed the secondary structure with the hydrophobic profile, confirming that all have hydrophilic properties highly conserved among proteins. The greatest difference was observed in the NTE and CTE regions. Another aspect studied was the comparison and analysis of tertiary structures. In our knowledge, this is the first time that these analyses were performed in such a comprehensive manner.